Peranan Kelompok Sadar Wisata Gerude Care Belitong dalam Pengembangan Destinasi Wisata Tanjung Kelayang - Nungky Puspita; Yuwana M. Marjuka; Meiti Azmi Efenly (Fakultas Pariwisata Universitas Pancasila, 2017)
Community Based Tourism is a tourism development concept that is adopted at Tanjung Kelayang Beach, Belitung Island. Through this concept it is expected that people living around the beach vicinity can participate in tourism from the planning process up to its implementation. The purpose of this research is to describe local people’s participation in developing the destination, their motivation to participate, and the form of participation. Using qualitative research method, this research employs a participant observation approach in collecting the data. The research finds that local people participate in tourism development by forming a community organization named Gerude Care Belitong. The organization develops a work program which guides them in conducting activities such as organizing event and participating in tourism service provision at Tanjung Kelayang beach.